An efficient protocol for the synthesis of monofluoroalkylated (hetero)arenes via Pd-catalyzed α-(hetero)arylation of α-fluoroketones with (hetero)aryl bromides. Issue 23 (4th June 2020) - Ding, Licheng; Han, Shuaijun; Chen, Xiaoyu; Li, Linlin; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Graphical abstract: Highlights: A new approach to synthesize α-(hetero)aryl-α-fluoroketones and monofluoroalkylated N -heteroarenes. The catalytic system features a low catalyst loading. Easily prepared monofluoroalkyl reagents. The debenzoylation step proceeds smoothly. Abstract: An efficient synthesis of monofluoroalkylated N -heteroarenes using α-fluoroketones as monofluoroalkyl reagents was developed. A variety of novel α-(hetero)aryl-α-fluoroketones and monofluoroalkylated N -heteroarenes were obtained in moderate to good yields. Notable advantages of this protocol include a low catalyst loading, easily prepared monofluoroalkyl reagents and wide substrate scope.